A DESCRIPTIVE STUDY ON TEACHING READING TO THE SIXTH YEAR STUDENTS OF SDN 51 KIDUL BETENG SURAKARTA IN 2010/2011 ACADEMIC YEAR - WIDIANINGTYAS, AGUSTIN (2011)
This research aims at describing the process of teaching-learning reading at the sixth year of SD Negeri Kidul Beteng 51 Surakarta. It is conducted to describe the process, goal, material, and the methods of teaching reading, the problems faced by the teacher, and the problem solving applied by the teacher at SD Negeri Kidul Beteng 51 Surakarta. The writer gets the data of this research from event, informant, and document. The techniques of collecting data are interview and observation, and documentation. The data are achieved from information related to the process of teaching-learning reading, in form of field note, interview scripts and document. The result of the analysis shows that the goal of teaching reading is to improve the reading competence of the students. The materials for teaching reading are using the descriptive text and new words about the material. The methods applied by the teacher are Situational Language Teaching, Grammar Translation Method, and Genre Based Approach. The teacher faces several problems in teaching reading, namely: class management, students' different ability in acquiring reading, and different motivation of the students. The problem solvings applied by the teacher are by walking around the class, giving advice and motivation about the importance of their activity in reading class, giving more exercises, and giving more time to teach reading.